2020
DOI: 10.1111/1365-2745.13330
|View full text |Cite
|
Sign up to set email alerts
|

Mass ratio effects underlie ecosystem responses to environmental change

Abstract: 1. Random species loss has been shown experimentally to reduce ecosystem function, sometimes more than other anthropogenic environmental changes. Yet, controversy surrounds the importance of this finding for natural systems where species loss is non-random.2. We compiled data from 16 multi-year experiments located at a single native tallgrass prairie site. These experiments included responses to 11 anthropogenic environmental changes, as well as non-random biodiversity loss either the removal of uncommon/rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 70 publications
4
40
0
Order By: Relevance
“…While the effects of shifts in plant community composition and loss of diversity on C cycling have received growing attention (Chen et al 2016, Li et al 2018, Smith et al 2020), how these effects vary across ecosystems is not well understood. Removal experiments, where the same plant species or functional groups are removed across different environmental settings, have shown that the effect of removals on drivers of C cycling (i.e., soil respiration, litter decomposition rates, net primary productivity) vary along abiotic and biotic gradients, including gradients in ecosystem productivity (Wardle and Zackrisson 2005, Fanin et al 2018) and nutrient availability (Suding et al 2008, McLaren and Turkington 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While the effects of shifts in plant community composition and loss of diversity on C cycling have received growing attention (Chen et al 2016, Li et al 2018, Smith et al 2020), how these effects vary across ecosystems is not well understood. Removal experiments, where the same plant species or functional groups are removed across different environmental settings, have shown that the effect of removals on drivers of C cycling (i.e., soil respiration, litter decomposition rates, net primary productivity) vary along abiotic and biotic gradients, including gradients in ecosystem productivity (Wardle and Zackrisson 2005, Fanin et al 2018) and nutrient availability (Suding et al 2008, McLaren and Turkington 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the positive effects of N enrichment on forage quality were not mowingdependent as mentioned above, mowing did diminish the positive effects of N enrichment on the quantity of nutrition provided in grasslands. While mass ratio effect is important in driving the quantitative responses of forage production to N addition (Smith et al 2020), our results indicate that it might not be the case for qualityadjusted yield, at least for the stocks of crude protein and crude fat examined here.…”
Section: Discussionmentioning
confidence: 59%
“…they act as 'foundation species', Ellison & Degrassi 2017), understanding the autecology and dynamics of dominant species in response to global change drivers appears to be a key research need. Indeed, the uncertainty around common species responses highlights that longterm cover/abundance trends need to be quantified if future ecosystem stability is to be understood, a call that has been made repeatedly in the literature (Smith & Knapp 2003;Gaston & Fuller 2007;Gaston 2011;Smith et al 2020). Monitoring species' local abundance may therefore better inform species' extinction risks in alpine areas under global change than monitoring their range (Cotto et al 2017).…”
Section: Discussionmentioning
confidence: 99%